2004
DOI: 10.1111/j.1439-0264.2003.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Basilar Artery of the Capybara (Hydrochaeris hydrochaeris): an Ultrastructural Study

Abstract: The present study investigated the ultrastructural features of the basilar artery of the largest rodent species, the capybara. The study suggests that the general ultrastructural morphological organization of the basilar artery of the capybara is similar to that of small rodents. However, there are some exceptions. The basilar artery of the capybara contains a subpopulation of 'granular' vascular smooth muscle cells resembling monocytes and/or macrophages. The possibility cannot be excluded that the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…In young capybaras, the fine structure of perivascular nerves, consisting of axons and Schwann cells, recorded in this study agrees with the previously observed features of cerebrovascular nerves in this animal [Islam et al, 2004] or autonomic nerves in general [Burnstock and Iwayama, 1971]. Hence the presence of characteristic both agranular and granular vesicles in axon varicosities and the appearance of Schwann cells were classic.…”
Section: Perivascular Nerve Structuresupporting
confidence: 81%
See 4 more Smart Citations
“…In young capybaras, the fine structure of perivascular nerves, consisting of axons and Schwann cells, recorded in this study agrees with the previously observed features of cerebrovascular nerves in this animal [Islam et al, 2004] or autonomic nerves in general [Burnstock and Iwayama, 1971]. Hence the presence of characteristic both agranular and granular vesicles in axon varicosities and the appearance of Schwann cells were classic.…”
Section: Perivascular Nerve Structuresupporting
confidence: 81%
“…This study also revealed that the ET-1-positive perivascular nerves, including both axon profiles and accompanying Schwann cells, underwent changes at animal maturation coinciding with ICA regression. Our findings, therefore, supplement our previous data on the fine structure of the BA in capybaras and to the artery changes during animal maturation and ICA regression [Islam et al, 2004;Loesch et al, 2005;Steele et al, 2006]. It should be mentioned, however, that it has previously been demonstrated that in a large proportion of capybaras at maturation (which is at about 1 year of age), the ICA is no longer functioning efficiently due to the collapsed lumen, decreased lumen size and transformation to a ligamentous cord.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations